Le territoire limnique, une alternative à la gouvernance des plans d’eau par masses d’eau ? - Pascal Bartout; Laurent Touchart (VertigO, 2017)
The current governance of bodies of water within French territory by "water masses" and "watersheds" is the result of a rich history, both scientific and regulatory. However, it proves unsatisfactory in its failure either to take into account limnological diversity or to integrate the lentic question within a codified approach which is preferentially and partially potamological. Hence, the question arises of the relevance of the spatial perimeters used. A geographical, geosystemical, then regional approach based around ‘water territories' has allowed research and mentalities to develop, but the multiplicity of territories generated constitutes a brake against the questioning of the power of hydraulic engineers. And yet, by fully integrating systemic approaches and those of the social sciences, it is possible to consider malleable forms of regionalization according to the criteria and periods and more appropriate to the objectives of "good water status" which have been set at the European level. The widening of limnological science to cover man-made lakes, ponds and other wetlands (instead of the only referring to lakes) opens new perspectives in the broader context of the role of water within the climatic fluctuations. Thereby gaining a broader understanding of the morphological and spatial diversity of the lentic corpus, it becomes possible to observe both systemic and spatial discontinuities and hence to discuss their origins or palimpsest character. The territorialization of these human-environment-body of water relationships thus produces a new concept, the limnic territory, which aims at being operational.